Optimization of palm oil extraction from decanter cake using Soxhlet extraction and effects of microwaves pre-treatment on extraction yield and physicochemical properties of palm oil - Tie, Hieng Ong; Hamzah, Muhammad Hazwan; Che Man, Hasfalina (Rynnye Lyan Resources, 2021)
Response Surface Methodology (RSM) was applied to study the optimum condition of palm oil extraction from oil palm decanter cake (OPDC) using Soxhlet extraction and nhexane as solvent. The main objective of this study was to achieve maximum oil extraction by determining the optimum of two parameters such as reaction time and solid to solvent ratio. The optimum parameters were found to be at 4.92 hrs of reaction time and solid to solvent ratio of 1:10. The proposed model shows R2 value of 0.78 where the experimental parameters were significant to the result. The optimized data was employed for comparison of oil yield for OPDC without and with microwave pre-treatment. OPDC with microwave pre-treatment yielded 3.289±0.047 g of palm oil which was higher than OPDC without microwave pre-treatment which yielded only 3.107±0.085 g of palm oil. Fourier Transform Infrared Spectroscopy (FTIR) analysis also revealed the abundance of C-H alkene stretch and C=O stretch, two major functional groups indicated the presence of fatty acid within the palm oil derived from both samples. Scanning electron microscopy (SEM) of decanter cake provided evidence that the OPDC with pre-treatment has more shrinkage on the surface after Soxhlet extraction compared to OPDC without pretreatment. Results of this study revealed that RSM helps to optimize parameters in agricultural processing.